A Framework for an Adaptive Anomaly Detection System with Fuzzy Data Mining - Xiang, Gao; Min, Wang; Rongchun, Zhao (Wuhan University journal of natural sciences, 2006)
In this paper, we present an adaptive anomaly detection framework that isapplicable to network-based intrusion detection. Our framework employs fuzzy cluster algorithm to detect anomalies in an online, adaptive fashion without a priori knowledge of the underlying data. We evaluate our method by performing experiments over network records from the KDD CUP99 data set.